Strategies for Improving Employee Performance Through Organizational Culture and Transformational Leadership with Job Satisfaction as an Intervening Variable: A Study of Employees in the Sewing Section of a Bekasi Garment Company - Utami, Dwi; Yusnita, Nancy; Hidayat, Yayan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze Employee Performance Improvement (Z) through Organizational Culture and Transformational Leadership, with Job Satisfaction as an intervening variable: Study of PT Sabena Cipta, Bekasi on Sewing Department Employees). The research population has 400 people, with a sample of research is 200 employees in the sewing department. The method used in this research uses quantitative methods, data collection for each variable studied uses a questionnaire with a rating scale. Data analysis techniques use descriptive statistics and path analysis techniques. The research results show: a) There is a direct positive influence of organizational culture on employee performance. b) There is a direct positive influence of transformational leadership on employee performance. c) There is a direct positive influence of job satisfaction on employee performance. d) there is a direct positive influence of organizational culture on job satisfaction e) There is a positive direct effect of transformational leadership on job satisfaction. f) there is an indirect positive influence of organizational culture on employee performance through job satisfaction. With a zcount value greater than ztable it can be concluded that job satisfaction mediates the influence of organizational culture on employee performance. g) there is an indirect positive influence of transformational leadership on employee performance through job satisfaction with a zcount value greater than ztable so it can be concluded that job satisfaction mediates the influence of transformational leadership on employee performance.